Performansi Green Inhibitor Berbasis Ekstrak Propolis Terhadap Laju Korosi Sambungan Las AISI 304-AISI 1037 Pada Medium Korosif Air Laut - Pratama, Krisna Yudha; Budiarsa, I Nyoman; Parwata, I Made (Teknik Desain Mekanika; Vol 13 No 1 (2024): Januari 2024 : Teknik Desain Mekanika, 2024)
Abstractt In this study, an experimental research method was applied, namely conducting immersion testing in seawater corrosive medium on 4 specimens of spot welded plates that were given variations in the concentration of applying corrosion inhibitors from propolis extract by 0 ml, 2 ml, 4 ml, and 6 ml. The propolis used is Kele-kele bee propolis (Trigona Sp.) from Lombok area. Natural-based inhibitor was chosen because it is environmentally friendly, easily available, and relatively inexpensive. The results of corrosion rate testing during 14 days immersion found that specimen with inhibitor concentrations of 2 ml (in 1000 ml seawater medium) had the highest inhibitor efficiency of 41.046%, followed by specimens with inhibitor concentrations of 6 ml of 17.274% and 4 ml of 16.482%. Keywords: Natural-Based Inhibitor, Propolis, Corrosion Rate Testing, Kele-Kele, Trigona Sp.